Newborn of mothers affected by autoimmune thyroiditis: the importance of thyroid function monitoring in the first months of life - Mosca Fabio; Corbetta Carlo; Corrias Andrea; Maina Ludovica; Passoni Arianna; Giovanettoni Chiara; Vigone Maria; Rovelli Rosanna; Chiumello Giuseppe; Weber Giovanna (BMC, 2010)
Abstract Background evaluation of thyroid function in neonates born from mothers affected by autoimmune thyroiditis in order to define if a precise follow-up is necessary for these children. The influence of maternal thyroid peroxidase antibody (TPOAb) and L-thyroxine therapy during pregnancy on neonatal thyroid function was also investigated. Methods 129 neonates were tested for thyroid function by measurement of free thyroxine (FT4) and thyroid stimulating hormone (TSH) in 3th day, 15th day and at one month of life. TPOAb were measured in all patients; periodical control of thyroid function were performed until 6 months of life if Ab were positive. Data concerning etiology of maternal hypothyroidism and maternal replacement therapy with L-thyroxine during pregnancy were retrospectively collected. Results 28% neonates showed at least a mild increase of TSH value at the different determinations. In the majority of them, a spontaneous completely normalisation of TSH value was observed within the first month life. L-thyroxine replacement therapy was started in 3 neonates. TPOAb titer and maternal L-thyroxine replacement therapy were not related to alteration of thyroid hormone function in our study population. Conclusions transient mild elevation of serum TSH above the normal reference value for age is frequently observed in the first month of life in infants born from mothers affected by autoimmune thyroiditis. Persistent hyperthyrotropinemia requiring replacement therapy is observed in 2.2% of these neonates. According to our experience, follow-up is recommended in these newborns; the most accurate and not invasive way to carefully monitor these infants after neonatal screening for CH seems to be serum-testing TSH between 2ndand 4th week of life.